Irreversible pulpitis in mature permanent teeth: a cost-effectiveness analysis of pulpotomy versus root canal treatment - Nighat Naved; Fahad Umer; Asif R. Khowaja (BMC, 2024)
Abstract Introduction Evidence-based dentistry suggests pulpotomy as a potential alternative to root canal treatment in mature permanent teeth with irreversible pulpitis. However, the evidence surrounding the cost-valuation and cost-efficacy of this treatment modality is not yet established. In this context, we adopted an economic modeling approach to assess the cost-effectiveness of pulpotomy versus root canal treatment, as this could aid in effective clinical decision-making. Methods A Markov model was constructed following a mature permanent tooth with irreversible pulpitis in an 18-year-old patient over a lifetime using TreeAge Pro Healthcare 2022. Transition probabilities were estimated based on existing literature. Costs were estimated based on the United States healthcare following a private-payer perspective and parameter uncertainties were addressed using Monte-Carlo simulations. The model was validated internally by sensitivity analyses, and face validation was performed by an experienced endodontist and health economist. Results In the base case scenario, root canal treatment was associated with additional health benefit but at an increased cost (1.08 more years with an incremental cost of 311.20 USD) over a period of an individual's lifetime. The probabilistic sensitivity analysis revealed pulpotomy to be cost-effective at lower Willingness-To-Pay (WTP) values (99.9% acceptable at 50 USD) whereas increasing the values of WTP threshold root canal treatment was a cost-effective treatment (99.9% acceptable at 550 USD). Conclusion Based on current evidence, pulpotomy was a cost-effective treatment option at lower WTP values for the management of irreversible pulpitis in mature permanent teeth. However, by increasing the WTP threshold, root canal treatment became a more cost-effective treatment option over a period of lifetime of an individual.